Development of two major resources for pea genomics: the GenoPea 13.2K SNP Array and a high‐density, high‐resolution consensus genetic map. (December 2015) - Tayeh, Nadim; Aluome, Christelle; Falque, Matthieu; Jacquin, Françoise; Klein, Anthony; Chauveau, Aurélie; Bérard, Aurélie; Houtin, Hervé; Rond, Céline; Kreplak, Jonathan; Boucherot, Karen; Martin, Chantal; et al.
Summary: Single nucleotide polymorphism (SNP) arrays represent important genotyping tools for innovative strategies in both basic research and applied breeding. Pea is an important food, feed and sustainable crop with a large (about 4.45 Gbp) but not yet available genome sequence. In the present study, 12 pea recombinant inbred line populations were genotyped using the newly developed GenoPea 13.2K SNP Array. Individual and consensus genetic maps were built providing insights into the structure and organization of the pea genome. Largely collinear genetic maps of 3918–8503 SNPs were obtained from all mapping populations, and only two of these exhibited putative chromosomal rearrangement signatures. Similar distortion patterns in different populations were noted. A total of 12 802 transcript‐derived SNP markers placed on a 15 079‐marker high‐density, high‐resolution consensus map allowed the identification of ohnologue‐rich regions within the pea genome and the localization of local duplicates. Dense syntenic networks with sequenced legume genomes were further established, paving the way for the identification of the molecular bases of important agronomic traits segregating in the mapping populations. The information gained on the structure and organization of the genome from this research will undoubtedly contribute to the understanding of the evolution of the pea genome and to its assembly. The GenoPea 13.2K SNP Array and individual and consensus genetic maps are valuable genomic tools for plant scientists to strengthen pea as a model for genetics and physiology and enhance breeding. Significance Statement: Pea is an important legume and model plant, but its large, transposon‐rich genome has delayed development of genomic resources. Here we describe key genomic tools that facilitate insights about genome organization, duplication patterns, structural rearrangements, and segregation distortion signatures. These resources will be useful for gene discovery and synteny‐based cloning approaches, and for surveys of genome evolution, genome‐wide association studies, and genomic selection strategies.